Inadequate food literacy is related to the worst health status and limitations in daily life in subjects with inflammatory bowel disease. (December 2022) - Fiorindi, Camilla; Coppolino, Giuseppe; Leone, Salvatore; Previtali, Enrica; Cei, Giulia; Luceri, Cristina; Ficari, Ferdinando; Russo, Edda; Giudici, Francesco
Summary: Purpose: Diet affects Inflammatory Bowel Disease (IBD) patients' quality of life. An adequate Food Literacy (FL) level enables adequate food choices. Currently, there is a lack of knowledge on the FL degree in patients with IBD. To deepen this item, we measured for the first time the degree of FL in IBD patients and then we analyzed its correlation with health and socio-demographic variables. Methods: This is an observational prospective study includingsubjects with IBD belonging to A.M.I.C.I. ONLUS association. We first measured the degree of FL through Literacy Survey (FLS-IT) questionnaire (containing the Newest Vital Sign (NVS)). In addition, we analyzed the relationship between FL individual level and health and sociodemographic variables, evaluating which of these aspects have a positive or negative correlation with FL level. In detail, continuous variables were analyzed by Mann Whitney test. Differences among proportions were assessed using the chi-square test. A Spearman's rank correlation analysis was performed to correlate the sociodemographic and health status variable with FL index and NVS. A stepwise linear regression analysis with backward selection was performed to identify possible predictor of good food literary skills in IBS patients. Results: Overall, 450 IBD subjects completed the FLS-IT questionnaire. Among them, 69.78% (n = 314) showed an inadequate FL level. Concerning NVS test, 14.22% showed an insufficient ability to interpret food labels. In addition, higher FL level was associated to better subjective health conditions (r = 0.1513; p = 0.0013), less limitations in daily living activities (r = 0.1430; p = 0.0026), higher physical activity (r = 1200; p = 0.0110) and no alcohol consumption (p = 0.0020). Finally, higher NVS scores were shown by women (r = 0.1408; p = 0.0028) and by younger subjects (r = −0.1686; p = 0.0003). Conclusions: We showed that an inadequate level of FL, related to the worst health status and the presence of several limitations in daily life, is widespread among our Italian cohort of IBD patients, and health and social status influence the ability to make adequate food choices. For this reason, it is necessary to investigate the problem and identify effective intervention strategies that will improve the patient's nutritional awareness.